2017
DOI: 10.1590/0102-311x00078515
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with physical violence against pregnant women from São Luís, Maranhão State, Brazil: an approach using structural equation modeling

Abstract: The factors associated with physical violence against pregnant women were analyzed in a cross-sectional study of 1,446 pregnant women from a prenatal cohort who were interviewed in 2010 and 2011 in São Luís, Brazil. In the initial model, socioeconomic status occupied the most distal position, determining sociodemographic factors, social support and the behavioral factors that ultimately determined physical violence, which was investigated as a latent variable. Structural equation modeling was used in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
3
0
4
Order By: Relevance
“…This result is consistent with recent studies reporting IPV prevalence rates (psychological, physical and/or sexual) during pregnancy between 3% and 57% 14,[32][33][34][35] . The prevalence of psychological violence (12.6%; CI:9.5-15.7) was below that identified in the literature, between 16% and 46.9% 15,16 .…”
Section: Fewer Than Nine Years Referencesupporting
confidence: 93%
“…This result is consistent with recent studies reporting IPV prevalence rates (psychological, physical and/or sexual) during pregnancy between 3% and 57% 14,[32][33][34][35] . The prevalence of psychological violence (12.6%; CI:9.5-15.7) was below that identified in the literature, between 16% and 46.9% 15,16 .…”
Section: Fewer Than Nine Years Referencesupporting
confidence: 93%
“…3,10 Contudo, as mais jovens, com baixas escolaridade e renda, com histórico de vitimização antes da gestação e que presenciaram suas mães serem agredidas pelo parceiro íntimo têm sido apontadas como as mais vulneráveis à violência na gravidez. 11,12 Início precoce da atividade sexual, ter três ou mais filhos, 13…”
Section: Métodosunclassified
“…2 A violência por parceiro íntimo (VPI) associa-se a estresse pós--traumático, uso abusivo de álcool e drogas ilícitas, infecções sexualmente transmissíveis (IST), depressão, ideações suicidas e morte. 3,4 referência de múltiplos parceiros sexuais, 11 gravidez não planejada, 7 aborto induzido ou tentativa de interromper a gestação 8 também são relacionados como fatores associados à violência no período gestacional. Além disso, uso de álcool e substâncias ilícitas, baixa escolaridade, condições socioeconômicas desfavoráveis e desemprego do parceiro íntimo determinam maior risco de sofrer VPIG.…”
Section: Introductionunclassified
“…It is one of common problems during pregnancy, although it is not one of the complications, such as preeclampsia and diabetes, which are routinely investigated 7 . The prevalence of IPVP varies depending on the methods used in studies and sociocultural characteristics and is observed in a wide range between 0.9% and 57.1% 7,8 . In the systematic review in which Gazmararian et al 9 examined 13 relevant studies, they found the prevalence of IPVP to be between 0.9% and 20.1%.…”
Section: Introductionmentioning
confidence: 99%
“…In the meta‐analyses related to IPVP in the literature, it was found that violence during pregnancy was associated with socioeconomic and demographic factors and was more frequently associated with data such as age, educational level, employment status, level of income, unintended pregnancy, prenatal care status, smoking, number of children, and parity 7,11 …”
Section: Introductionmentioning
confidence: 99%